2019
DOI: 10.3390/f10100830
|View full text |Cite
|
Sign up to set email alerts
|

Dark Septate Endophyte Improves Drought Tolerance of Ormosia hosiei Hemsley & E. H. Wilson by Modulating Root Morphology, Ultrastructure, and the Ratio of Root Hormones

Abstract: Dark septate endophytes (DSEs) are known to help host plants survive drought stress; however, how DSEs enhance host plant drought resistance under water stress conditions remains unclear. The objective of this study was to inoculate Ormosia hosiei seedlings with a DSE strain (Acrocalymma vagum) to investigate the effects of DSE inoculation on root morphology, ultrastructure, and the endogenous hormone content under drought stress conditions and to elucidate the drought resistance mechanism involved in the DSE–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…The root meristem constitutes the main site of HM action and also rapidly synthesizes a great deal of ABA. The inhibition of plant growth, which was induced by HM stress, is also in part a result of the increased ABA concentration (Liu and Wei, 2019). In this study, the contents of IAA and ABA were obviously increased.…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…The root meristem constitutes the main site of HM action and also rapidly synthesizes a great deal of ABA. The inhibition of plant growth, which was induced by HM stress, is also in part a result of the increased ABA concentration (Liu and Wei, 2019). In this study, the contents of IAA and ABA were obviously increased.…”
Section: Discussionsupporting
confidence: 48%
“…It was suggested that hormones, released by mycorrhizal fungi, may contribute to the enhancement of plant growth (Frankenberger and Arshad, 1995). Phytohormones responded synergistically to HM stress conditions by regulating their synthetic ability, changing the hormone content, and adjusting the balance and ratio of hormones, in which the ratios of the stress-related phytohormones often have more profound implications than does the role of a single phytohormone in plants (Liu and Wei, 2019). Barker and Tagu (2000) verified that changes in the phytohormone ratios affected the different stages of plant development, which were closely related to mycorrhizal symbiosis.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations